2017
DOI: 10.1111/acer.13350
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Anxiety Sensitivity, and Perceived Stress as Predictors of Recent Drinking, Alcohol Craving, and Social Stress Response in Heavy Drinkers

Abstract: BackgroundStress and anxiety are widely considered to be causally related to alcohol craving and consumption, as well as development and maintenance of alcohol use disorder (AUD). However, numerous preclinical and human studies examining effects of stress or anxiety on alcohol use and alcohol‐related problems have been equivocal. This study examined relationships between scores on self‐report anxiety, anxiety sensitivity, and stress measures and frequency and intensity of recent drinking, alcohol craving durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 61 publications
4
46
0
2
Order By: Relevance
“…Specifically, positive affective responses to acute exercise are generally associated with greater exercise participation, while negative mood states predict lower participation to exercise regimes ( 29 ). Of importance, it is also known that lowered mood states and anxiety frequently precipitate “urges” to drink alcohol, which in turn can trigger the onset of heavy drinking in people with AUD ( 30 , 31 ). To date, however, only two studies have examined the acute effects of exercise in alcohol dependent individuals.…”
Section: Five Key Research Questionsmentioning
confidence: 99%
“…Specifically, positive affective responses to acute exercise are generally associated with greater exercise participation, while negative mood states predict lower participation to exercise regimes ( 29 ). Of importance, it is also known that lowered mood states and anxiety frequently precipitate “urges” to drink alcohol, which in turn can trigger the onset of heavy drinking in people with AUD ( 30 , 31 ). To date, however, only two studies have examined the acute effects of exercise in alcohol dependent individuals.…”
Section: Five Key Research Questionsmentioning
confidence: 99%
“…Further research is required to understand more clearly how AS reduces drinking in adolescence. Given that previous research has found positive associations between AS and drinking in adult populations , further research is also required to identify the age at which AS becomes a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in effort and motivation are related to health risk behaviors such as addictions, alcohol consumption, poor eating habits, and violence [17][18][19]. These behaviors in turn cause physical problems and increase emotional health problems [20,21].…”
Section: Academic Achievement Relation With Healthmentioning
confidence: 99%